Soundbreaking [videorecording (DVD)] : stories from the cutting edge of recorded music - Mulroney, Dermot (Athena, 2016)
Music has been a constant in human history, an intermingling of voice and instrument that for all its local variation and increasing sophistication nevertheless endured in more or less the same form for centuries. Then came recording--and music was forever transformed. Soundbreaking, an eight-part event television series, traces this ongoing sonic revolution, and explores the nexus of cutting-edge technology and human artistry that has created the soundtrack of our lives. Featuring more than 160 original interviews with some of the most celebrated recording artists, producers, and music industry pioneers of all time, Soundbreaking charts a century's worth of innovation and experimentation, and offers a behind-the-scenes look at the birth of brand new sounds. From the Beatles' groundbreaking use of multi-track technology to the synthesized stylings of Stevie Wonder, from disco-era drum machines to the modern art of sampling, the series highlights the dynamic tension between the artificial and the natural--between the man-made and the god-given--and explores the way in which that tension has continuously redefined not only what we listen to and how we listen to it, but our very sense of what music is and can be. In the end, Soundbreaking makes us hear the songs we love in a whole new way, and illuminates the sonic alchemy by which the music we listen to becomes a fundamental part of who we are.